Seeing water as a central element in genesis 1-9. Its significance for ecological discourse in the african context - Ijezie, Luke (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
An attentive study of the accounts of the origins in Genesis 1-9 discovers the centrality of the element water in the creation, preservation, destruction and further restoration of all things. The accounts present water as a great force in all its ramifications. The Creator realises this great potentiality of water and takes extra care in putting it under effective control and management so that it serves the creative purpose. Everything in creation is seen to thrive as long as water is put to effective use. Interestingly the same water is used to destroy creation and to preserve it. All these challenge greater consciousness and discussion on the role of water in the ecological discourse. All talk of environmental health goes back to the effective use of water. Unfortunately, water remains a scarce commodity in the African context not only because of drought and allied natural causes but due more to recklessness on the human agents who should have put it to greater control and management. Many parts of Nigeria are blessed with natural sources of water, yet, people suffer terribly for lack of water. The present essay, using a synchronic reading approach, examines the role of water in Genesis 1-9 and its abiding lessons for the present ecological discussions.